Delayed trait development and the convergent evolution of shell kinesis in turtles. Issue 1888 (3rd October 2018) - Cordero, Gerardo A.; Quinteros, Kevin; Janzen, Fredric J.
Abstract : Understanding developmental processes is foundational to clarifying the mechanisms by which convergent evolution occurs. Here, we show how a key convergently evolving trait is slowly 'acquired' in growing turtles. Many functionally relevant traits emerge late in turtle ontogeny, owing to design constraints imposed by the shell. We investigated this trend by examining derived patterns of shell formation associated with the multiple (at least 8) origins of shell kinesis in small-bodied turtles. Using box turtles as a model, we demonstrate that the flexible hinge joint required for shell kinesis differentiates gradually and via extensive repatterning of shell tissue. Disproportionate changes in shell shape and size substantiate that this transformation is a delayed ontogenetic response (3–5 years post-hatching) to structural alterations that arise in embryogenesis. These findings exemplify that the translation of genotype to phenotype may reach far beyond embryonic life stages. Thus, the temporal scope for developmental origins of adaptive morphological change might be broader than generally understood. We propose that delayed trait differentiation via tissue repatterning might facilitate phenotypic diversification and innovation that otherwise would not arise due to developmental constraints.